The Assessment of Fixed Orthodontic Treatment Successfulness Using American Board of Orthodontics System in Airlangga University Dental Hospital - Ardani, I Gusti Aju Wahju; Nugroho, Dimas Iman; Ramadhani, Fakhma Zakki; Narmada, Ida Bagus (Faculty of Dental Medicine Universitas Airlangga, 2021)
Background: The purpose of orthodontic treatment is to improve efficient function, tissue balance, and obtain harmonious facial aesthetic results so the successfulness of orthodontic treatment should be comprehensive because maloclusion can occur in dentoalveolar, skeletal and soft tissue tissues. Purpose: This study aims to evaluate the successfulness of orthodontic treatment using fixed orthodontic appliances in Orthodontic Clinic Dental Hospital, Faculty of Dental Medicine Universitas Airlangga by means of ABO system. Methods: Descriptive analytic by comparing the data before and after treatment, then the sample was divided into 3 based on the skeletal malocclusion group. Dental efficacy was measured using the ABO system and the Bolton anterior ratio. Skeletal success by looking at ANB, FHI, and proportion of anterior facial height (UAFH: LAFH). Meanwhile, the success of the soft tissue was by seeing the changes in the aesthetic lines of the upper and lower lips. The statistics used in this study were Kruskal-Whallis for the ABO DI and OGS difference test, Spearman to determine the relationship between ABO DI and OGS measurement components and McNemar and Wilcoxon to determine the difference before and after treatment on all measurements. Results: Treatment of class I skeletal malocclusion had the best mean ABO OGS score. Class II and III treatments had significant treatment advancements. In other measurements, there are significant differences after treatment at FHI in class I, (UAFH: LAFH) in class II and lower lip esthetic line in class II. Conclusion: Generally, the successfulness of orthodontic treatment in Orthodontic Clinic Dental Hospital, Faculty of Dental Medicine, Universitas Airlangga was adequate. In addition, the assessment of the successful orthodontic treatment needs to be adjusted to the standard values that can be accepted by a certain population, especially the Javanese population.